Pharmacovigilance imbalance analysis of VEGFR-TKI-related taste and smell disorders - Zhong-hua Fu; Chenglong Zhao; Yaqin Wang; Lei Zhang; Lei Wang (Scientific Reports)
Abstract Taste and smell disorders (TSDs) can induce diminished interest in food, inadequate nutrient intake, and emotional irregularities, particularly among cancer patients. Previous research found that the main culprits of TSD development in cancer patients are cytotoxic drugs such as taxol, fluorouracil, cyclophosphamide, and anthracycline-based drugs. The advent of targeted drugs such as vascular endothelial growth factor receptor-tyrosine kinase inhibitors (VEGFR-TKIs) has significantly extended the survival time of cancer patients, and thus widely used in clinical practice. However, the association between the use of VEGFR-TKIs and the development of TSDs havs not been studied.The adverse event(AE) reports related to VEGFR-TKIs were downloaded from the FDA Adverse Event Reporting System (FAERS) database. Disproportionality analysis was conducted to assess the correlation between VEGFR-TKIs and TSDs. The Standardized Medical Dictionary for Regulatory Activities (MedDRA) Queries (SMQs) were used to analyze the AEs of TSDs. The study found a statistically significant correlation between the occurrence of TSDs and the use of VEGF-TKIs (cabozantinib, axitinib, pazopanib, sunitinib, nintedanib, and lenvatinib).However, the instructions for Nintedanib, Sorafenib and Lenvatinib were not mentioned. Capbottinib demonstrated the highest number of reports(1790 cases), also with the strongest association (ROR 95%CI-low = 16.51; PRR = 16.18; IC025 = 3.96) when analyzing the narrow SMQ of TSDs. Dysgeusia, taste disorder, and ageusia were the most commonly reported preferred terms (PTs) in VEGFR-TKI-related TSDs, accounting for more than 90% of the reported cases. Cabozantinib showed the highest number of reports and strongest correlation with ageusia, taste disorder, parosmia, and anosmia. The study found significant association between the reports of TSDs and the use of VEGFR-TKIs, indicating the monitoring of TSD development and appropriate management in clinical is necessary.